Avaliação do extrato metanólico de urucum (Bixa orellana L.) em associação com azul de metileno para dupla coloração em histologia vegetal - Costa Leal, Davi Ângelo; Barreto Serra, Mariana; Brandão Campos, Matheus; Reis Sousa, Hiran; Assunção Barroso, Wermerson; Machado Vilanova, Crisálida (Scientia Plena, 2018)
The annatto is a yellow-orange dye extracted from the pulp of Bixa orellana L. seeds, a tree native of tropical forests. The composition of this dye consists basically of carotenoids, such as bixin, norbixin and nobixate. Bixin, a highest amount compound, has a liposoluble characteristic that facilitates its interaction with cell membranes. The present study evaluated the dye association viability in vegetable histology of Bixa orellana L., Morinda citrifolia L. and Petiveria alliacea L. leaves. The annatto dye was obtained by extraction in methanol (1:6 w/v) by maceration of Bixa orellana seeds. The analyzes were carried out in cross sections of the vegetal samples collected in the “Berta Lange Morretes” Medical Garden of Federal University of Maranhão (UFMA). After clarification with sodium hypochlorite, the staining was performed in an average immersion time of 10 seconds, for both the urucum + methylene blue association in the 2:1 (A1) and 1:1 (A2) concentrations as well as for the blue methylene 1% and annatto dye 2%. All sections were mounted between blade and coverslip with distilled water, and visualized under an optical microscope. The A1 allowed a better morphological visualization of the anatomical structures due to the acidic characteristic of bixin which reacts with basic pH components of plant, and the alkaline characteristic of methylene blue that reacts with structures of acidic nature. This association represents a staining technique that can contribute alternatively as plant histological dyes.